Redescription of Wyeomyia (Decamyia) felicia (Dyar & Núñez Tovar, 1927) and description of a new species of the subgenus from Trinidad (Diptera: Culicidae) - Ribeiro, Paulino Siqueira; Motta, Monique Albuquerque; Seiblitz, Giulia Caminha; Pereira, Glauber Rocha; Galvão, Cleber; Pecor, David Brooks; Lourenço-De-Oliveira, Ricardo (Zootaxa, 2022)
Mosquito species of the subgenus Decamyia Dyar, 1919 of genus Wyeomyia Theobald, 1901 are known to have immature stages mostly associated with Heliconia plants. Currently, the subgenus includes five species, some of which are poorly characterized. Here, we redescribe and illustrate the larval, pupal and adult life stages of Wy. felicia (Dyar & Núñez Tovar, 1927). In addition, Wyeomyia monticola, a new species of Decamyia from Trinidad, close to Wy. felicia, is described. The new species can be distinguished by morphological characters of the male genitalia, larva and pupa.